Antenatal maternal hepatitis B care is a predictor of timely perinatal administration of hepatitis B immunoglobulin. Issue 8 (August 2017) - Le, Suong T. T.; Sahhar, Lukas; Spring, Stephanie; Sievert, William; Dev, Anouk T.
Abstract: Background: Mother‐to‐child transmission of hepatitis B virus continues to occur despite universal recommendations for neonatal immune prophylaxis therapy (IPT) and infant vaccination. Aim: To characterise the risk factors for failure to provide timely IPT and completion of the infant hepatitis B vaccination schedule for children born to mothers with chronic hepatitis B (CHB). Methods: We conducted a retrospective cohort study to assess compliance with universal guidelines for neonatal IPT for children born to CHB mothers at Monash Health, Australia from 2008 to 2013. These mothers were invited to participate in a telephone interview regarding post‐partum hepatitis B virus (HBV) care and infant vaccination status. Multivariate logistic regression analysis was utilised to identify the predictors for engagement with specialist HBV care, timely administration of IPT, completion of HBV vaccination schedule and serological testing of the baby. Results: A total of 451 CHB mothers delivered 454 live births. HBV immunoglobulin (HBIg) was dispensed within 12 h in 79.52% of births. HBIg was not administered to eight neonates. Of the 451 women, 125 were interviewed: 88.8% of babies completed the vaccine schedule, and 19.2% of infants had post‐vaccination testing. Antenatal HBV care was independently associated with a greater likelihood of timely HBIg administration (odds ratio 1.64, P = 0.04, 95% CI: 1.03–2.61). There were no significant predictors for engagement with specialist HBV care, vaccine coverage or serological testing of the baby. Conclusion: Targeted interventions to improve timely HBIg and completion of the vaccine schedule are recommended. All pregnant women with CHB should be referred for HBV‐specific antenatal care regardless of viral replicative status.